Impact Of Psychological, Situational, Social, And Physiological Factors Affecting Dual Process Ethical Decision Making With A Mediating Role Of Emotional Regulations In Canada - Dr. Ana Atta (Migration Letters, 2024)
Introduction: Ethical decision-making is crucial for measuring human behaviour, impacting relationships, personal choices, and professional conduct. In the process of dual-process theories, ethical decision-making is based on two distinct procedures (Warner et al., 2022). However, the impact of various psychological, social, situational, and physiological factors on dual-process ethical decision-making has been widely studied, specifically in Canada (Toti et al., 2021). Methods: The data was collected from [1]384 respondents within the set criteria. The correlational and regression analysis tests were applied using Smart PLS software. This study is a primary quantitative study with the deductive approach. The validity and reliability of the data were measured using Cronbach Alpha, and the Average Variance was Extracted. Findings: The results show that all the variables have the strongest correlation, with values of 0.912, 0.868, 0.844, and 0.898, respectively. It has been indicated that emotional regulation also plays a significant mediating role in impacting the EDM, with a value of 0.838. Conclusion: It has been concluded that the hypothesis for the study is accepted as all the independent variables, namely psychological, situational, social and physiological factors, have a strong positive significant relationship with the dual process of ethical decision-making and have a significant impact.